2016
DOI: 10.1002/anie.201605615
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Alkyne Hydrosilylation and Sequential Vinylsilane Hydroboration with Markovnikov Selectivity

Ziqing Zuo,
Ji Yang,
Zheng Huang

Abstract: A pyridinebis(oxazoline) cobalt complex is a very efficient precatalyst for the hydrosilylation of terminal alkynes with Ph2 SiH2 , providing α-vinylsilanes with high (Markovnikov) regioselectivity and broad functional-group tolerance. The vinylsilane products can be further converted into geminal borosilanes through Markovnikov hydroboration with pinacolborane and a bis(imino)pyridine cobalt catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(76 citation statements)
references
References 69 publications
1
74
0
1
Order By: Relevance
“…[234,235] Employing OIP-(98) or PyBox-CoCl 2 (99-CoCl 2 ) complex as a precatalyst, Lu group [236] and Huang group [237] independently reported Markovnikov-type hydrosilylation of terminal alkynes, respectively (Scheme 85b). [234,235] Employing OIP-(98) or PyBox-CoCl 2 (99-CoCl 2 ) complex as a precatalyst, Lu group [236] and Huang group [237] independently reported Markovnikov-type hydrosilylation of terminal alkynes, respectively (Scheme 85b).…”
Section: Scheme 84 Co-catalyzed Hydrosilylation Of Internal Alkynesmentioning
confidence: 99%
“…[234,235] Employing OIP-(98) or PyBox-CoCl 2 (99-CoCl 2 ) complex as a precatalyst, Lu group [236] and Huang group [237] independently reported Markovnikov-type hydrosilylation of terminal alkynes, respectively (Scheme 85b). [234,235] Employing OIP-(98) or PyBox-CoCl 2 (99-CoCl 2 ) complex as a precatalyst, Lu group [236] and Huang group [237] independently reported Markovnikov-type hydrosilylation of terminal alkynes, respectively (Scheme 85b).…”
Section: Scheme 84 Co-catalyzed Hydrosilylation Of Internal Alkynesmentioning
confidence: 99%
“…Of special praise is the selective formation of Z-β-vinylsilanes in combination with the high tolerance of functional groups. Huang also reported the synthesis of α-vinylsilanes with high Markovnikov selectivity from the reaction of terminal alkynes with Ph2SiH2 using iminopyridine CoCl2 complexes [33]. Again, high Guo and Lu developed a cobalt catalyst with an unmatched turn-over frequency TOF of 65,520 h −1 for the hydrosilylation of alkynes ( Figure 11) [28].…”
Section: Cobalt Catalystsmentioning
confidence: 99%
“…Of special praise is the selective formation of Z-β-vinylsilanes in combination with the high tolerance of functional groups. Huang also reported the synthesis of α-vinylsilanes with high Markovnikov selectivity from the reaction of terminal alkynes with Ph 2 SiH 2 using iminopyridine CoCl 2 complexes [33]. Again, high selectivity could be observed concomitant with high functional group tolerance; the vinylsilanes could be reacted to germinal borosilanes in subsequent reactions.…”
Section: Cobalt Catalystsmentioning
confidence: 99%
“…However, control of stereo‐ and regioselectivity is the major issue hampering the widespread use of this method, largely because three possible hydrosilylation products, namely α‐, β‐(Z)‐, and β‐(E)‐vinylsilanes, can be generated in the hydrosilylation reaction of terminal alkynes, with the former being rarely obtained selectively . By now, some works about the formation of α‐vinylsilane had been published by theorists and experimenters . By inspection of these researches, we found that the metal‐catalysts were mainly introduced for catalyzing this hydrosilylation of alkynes, such as Co, Pt, and Ru .…”
Section: Introductionmentioning
confidence: 99%
“…Vinylsilanes are valuable building blocks in organic synthesis and material chemistry because of their versatile characters, such as low toxicity, high stability, facile manipulations, and a variety of transformations . Accordingly, methods for the preparation of vinylsilanes have gained increased attentions from synthetic chemists, in which the hydrosilylation of alkynes was considered as a simple and straightforward method . This hydrosilylation reaction involves the addition of a Si − H bond across a C − C triple bond, bringing an atom‐economical result with 100% atom efficiency.…”
Section: Introductionmentioning
confidence: 99%